Freehand drawing and discovery urban sketching and concept drawing for designers - Richards, James 1955- (Wiley, 2013)
While computer-aided design has changed the way designers explore and communicate their visions, freehand drawing remains an essential skill for capturing a flow of visual ideas and developing them on the spot. Freehand Drawing & Discovery takes an updated and practical approach to using hand sketching in a digital world, employing a "both/and" philosophy that shows you how to rapidly capture ideas with hand sketching that can then be further explored and refined using digital tools. Created by an urban designer and blog correspondent for Urban Sketchers, this resource-rich, user-friendly guide provides step-by-step instruction on drawing tools and techniques. It offers practical suggestions on how to use freehand sketching skills in conjunction with digital tools on real-world projects. Freehand Drawing & Discovery: Crosses disciplinary boundaries, from architecture, urban planning, and landscape architecture to the widely diverse Urban Sketching community. Covers sketching tools and techniques, location sketching, concept sketching, and digital sketching. Includes nearly 300 full-color drawings, including contributions by Michael Vergason, Kevin Sloan, Christine Ten Eyck, Luis Ruiz, Gabriel Campanario, Liz Steel, Kim Perry, Bob Hopewell, and a special contribution on digital design sketching by Robert Chipman. Features access to video tutorials in which the author demonstrates techniques for creating sketches from your imagination, on location, sketching on a digital tablet, and painting with watercolors. Freehand Drawing & Discovery is a must-have handbook for students and professionals in urban planning, landscape architecture, and architecture. It is also a rewarding resource for general artists, sketchers, and anyone interested in the Urban Sketching phenomenon.